Automatic Acquisition of Chinese-English Parallel Corpus from the Web - Zhang, Ying; Wu, Ke; Gao, Jianfeng; Vines, Phil (ACL/SIGPARSE, 2005)
Parallel corpora are a valuable resource for tasks such as cross-language information retrieval and data-driven natural language processing systems. Previously only small scale corpora have been available, thus restricting their practical use. This paper describes a system that overcomes this limitation by automatically collecting high quality parallel bilingual corpora from the web. Previous systems used a single principle feature for parallel web page verification, whereas we use multiple features to identify parallel texts via a k-nearest-neighbor classifier. Our system was evaluated using a data set containing 6500 Chinese[ English candidate parallel pairs that have been manually annotated. Experiments show that the use of a k-nearest-neighbors classifier with multiple features achieves substantial improvements over the systems that use any one of these features. The system achieved a precision rate of 95% and a recall rate of 97%, and thus is a significant improvement over earlier work.